The anacronic economic agenda of the Bolsonaro Government - Carneiro, Ricardo (Brazilian Keynesian Review, 2019)
The article analyzes, in an exploratory manner, the likely impacts of the Bolsonaro Government's economic agenda on growth and social inclusion by examining it in the light of a global context characterized by financialization and a domestic scenario dominated by stagnation. To this end, it highlights the main axes of this agenda and their possible effects: first, a fiscal effect encompassing the pension and the tax reforms and the new tax regime, including in the latter a proposal for radical untying of some former obligatory spending from the government budget; second, macroeconomic and financial effects, including the independence of the Central Bank, foreign exchange liberalization and a new financing pattern in which the dismantling of public banks is part; lastly, productive and distributive effects, including trade liberalization, privatization, infrastructure policy, the new round of labor reform and the minimum wage policy.